Perancangan Sistem Informasi Berita Otomotif Berbasis Website Dengan Php Dan Mysql - Tiert, Baruch Daniel; Dharmawan, Alexander; Gondohanindijo, Jutono (INTECOMS: Journal of Information Technology and Computer Science, 2024)
In today's digital era, information about the automotive world is in great demand by the public. To meet these needs, an information system is needed that is able to present automotive news quickly, accurately, and easily accessible. This research aims to design and develop a website-based automotive news information system using PHP and MySQL. This system is designed to facilitate users in getting the latest information about the automotive world, including news about new vehicles, product reviews, maintenance tips, and the latest technology. The methods used in developing this system include needs analysis, system design, implementation, and testing. The results show that the information system developed is able to provide automotive news services with a user-friendly interface and features that suit user needs. With this system, it is expected to increase the accessibility and dissemination of automotive information among the public.